Comic turn in contemporary English fiction who's laughing now? - Marsh, Huw ca. 20./21. Jh (Bloomsbury Academic, 2020)
"The Comic Turn in Contemporary English Fiction explores the importance of comedy in contemporary literature and culture. In an era largely defined by a mood of crisis, bleakness, cruelty, melancholia, environmental catastrophe and collapse, Huw Marsh argues that contemporary fiction is as likely to treat these subjects comically as it is to treat them gravely, and that the recognition and proper analysis of this humour opens up new ways to think about literature. Structured around readings of authors including Martin Amis, Nicola Barker, Julian Barnes, Jonathan Coe, Howard Jacobson, Magnus Mills and Zadie Smith, this book suggests not only that much of the most interesting contemporary writing is funny and that there is a comic tendency in contemporary fiction, but also that this humour, this comic licence, allows writers of contemporary fiction to do peculiar and interesting things - things that are funny in the sense of odd or strange and that may in turn inspire a funny turn in readers. Marsh offers a series of original critical and theoretical frameworks for discussing questions of literary genre, style, affect and politics, demonstrating that comedy is an often neglected mode that plays a generative role in much of the most interesting contemporary writing, creating sites of rich political, stylistic, cognitive and ethical contestation whose analysis offers a new perspective on the present."